Development of Membership Management Application for Fitness Center using Extreme Programming Methodology - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
This study aims to develop a responsive and efficient membership management application for fitness centers using the Extreme Programming (XP) methodology. Challenges in managing memberships at fitness centers include complex registration processes, difficulty tracking payments, and inefficient member data management. The methods used include system requirements analysis involving stakeholders, application design and implementation using XP approaches such as short iterations and continuous testing, and testing and evaluation involving internal teams and fitness center members. The result is an application that integrates essential features such as membership management, class scheduling, payments, member progress reporting, communication, and equipment reservations. Alpha and beta testing and member performance and responsiveness evaluations indicate that this application meets user expectations and enhances operational efficiency at fitness centers. This research contributes to providing a technological solution that improves membership management processes at fitness centers with a responsive and effective approach aligned with XP principles in software development.